The socio-economic effect ofcovid-19 on households in Epworth, Harare - Mashatise, Memory Tinotenda (University of the Witwatersrand, Johannesburg, 2024)
This research report explores how COVID-19 impacted households on a socioeconomic level. Epworth, a peri-urban suburb of Harare, was the study's research location. This study focuses on the Southern African context, where social distancing and lockdowns implemented by governments in order to curb the spread ofthe COVID-19 pandemic in the year(s) 2020, 2021, as well as 2022. Most specifically,the government of Zimbabwe, being the government, this study focuses on implemented measures that had persistent negative socioeconomic effect on households by disrupting livelihoods, businesses, and other sources of income. Sucheffects were not only experienced during COVID-19, but also in the after of the pandemic. Maslow's Hierarchy of Needs was utilized as a theoretical foundation to frame the research in examining how the COVID-19 epidemic affected Epworth households. The premise of Maslow's Hierarchy of Needs theory emphasizes the value of human needs and how implemented regulations led to scenarios where citizens lost opportunities for economic survival and stability for their individual and households' material well-being. Consequently, such a crucial point is well placed within Maslow's identified need for safety, and security. Literature reviewed specified that the weakened economy and social problems in Zimbabwe, such as unemployment, poverty, inadequate healthcare, and a lack of supplies for COVID-19 treatment, predominantly exacerbated the pandemic's adverse effects. Semi- structured interviews with 15 breadwinners in Epworth aged 18 to 64 were used for qualitative research. After interview transcription, the data was examined through thematic analysis. The findings of the research demonstrated the need for better access to essential services in the sense that the majority of individuals experienced restricted access to such services as a result of implemented lockdowns. Due to the COVID-19 pandemic's detrimental effects on people's freedom of association, mobility, people began adopting strategies including returning to live with relatives and lowering expenses. Furthermore, self-employed and employed people were found to have been severely affected by the outbreak of the pandemic. To support youth, notably breadwinners for children whose parents lost their lives and jobs due to COVID-19 effects, It is recommended that that the business sector and government authorities ought to create economic opportunities. Lastly, it is ii recommended that breadwinners diversify their sources of income.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; COVID-19; Vulnerable community; Households; Labour pools; Marginal urban spaces; Unemployment; Poverty; Breadwinner; Epworth; SDG-3: Good health and well-being; SDG-8: Decent work and economic growth